Inexpensive and flexible nanographene-based electrodes for ubiquitous electrocardiogram monitoring - Francisco J. Romero (Nature Portfolio, 2019)
Cheap graphene electrodes for biosignal monitoring A cheap graphene foam electrode has been shown to deliver both accurate acquisition and efficient processing of biosignal to enable next generation medical and wearable devices. A team led by Dr Francisco Romero from University of Granada, Spain develops a one-step and inexpensive method to make electrophysical electrodes for biocompatible signal transduction. They employ low diode lasers to selectively induce highly porous structures in the graphene foam on a flexible substrate. When combined with a clustering algorithm, the graphene foam electrodes can effectively suppress the artifact and noise signals and extract heart beat pattern with more than 90% accuracy. These results present delicate balance between the high accuracy data acquisition and efficient data processing, which are both important for the elemental devices in the internet-of-things paradigm.